A educação e a gestão na economia solidária: um estudo sobre os processos de formação das incubadoras tecnológicas de cooperativas populares - Daniel Calbino Pinheiro (2010)
This work aimed at understanding the conditions under which lie the work of education and knowledge transfer of technical and administrative policy made by technology incubators of popular cooperatives (ITCP's). Made this distinction, was proposed study how is education policy implemented by ITCP's. To constitute the epistemological basis of this work, we resorted to critical theory. As regards the methodology, relied on triangulation methods, making a quantitative and qualitative research. In quantitative research, we used a Survey. The results indicated that most activities of technical and policy occurs equally, formally and informally, for over three years, creating their own materials, and that all members participate in these processes. It was also reported that develop research projects, hold internal discussions, and has a political profile that supports the social economy as a counterpoint to the capitalist economy. The results also enabled the establishment of criteria for the selectionof three incubators for qualitative analysis: ITCP/UNEB, ITES/UFBA and INCOOP/UFSCar. In qualitative research, there were visits to three incubators, interviews with members and survey of secondary data. For the analysis of the results, we used the dialectical method andcontent analysis. By comparing the results of two surveys, there were contradictions with what was stated in the first phase, implying that only the use of quantitative method is not sufficient to develop this themes. Regarding the results of qualitative research, was confirmed that the incubators have developed training activities, technical and policy. However, about the activities of technical training, there are problems to systematize and create materials themselves, and to try to reframe the knowledge management has occurred in piecemeal fashion. It found also contradictions in the internal organization of the incubators. Despitepropose the self-managed, have contradictions with regard to power relations, collective decisions, divisions of labor, the compensation of its professionals, as well as the dynamics of the working day. It was also noted that incubators have had difficulty in carrying out internaldiscussions and training courses for teachers, and dependence have funding to carry out the process of incubation. Although some members has understanding the negative aspects of these processes seem to be few who encourage alternative proposals. Finally, it was confirmed that the conceptions of the three incubators is of counterpoint to the marketeconomy. However, few have developed strategies and theories of social change based on this perspective. Thus, it appears that the difficulty of formulating social theories, have to be reflected in the practice of incubators, hampering attempts to reframe knowledge management, limiting to organize themselves so self-managed and committing even the practices of incubation.